EFEKTIVITAS PENERAPAN AMDAL DALAM PENGELOLAAN LINGKUNGAN HIDUP PADA PEMBANGKIT LISTRIK DI BALI – STUDI KASUS PLTD/G PESANGGARAN - Helga Margareta Hunter; Made Sudiana Mahendra; I.G.B. Sila Dharma (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
EFFECTIVENESS OF AMDAL APPLICATIONS IN ENVIRONMENTAL MANAGEMENT ON ELECTRICAL GENERATOR IN BALI - CASE STUDY PLTD / G PESANGGARANThe development and sustainability of power plant’s activity has a positive impact, such as the increased electricity energy which will indirectly boost the economy, but it also has negative impact, such as the rising pressure towards environment. One way to prevent it from damaging environment is to require stakeholders and industry actors to have the environment permit including EIA (Environment Impact Assessment). The objective of this study was to find out the effectiveness of EIA application on power plant on PLTD/G Pesanggaran. This study was conducted with a descriptive qualitative approach which used data from observations, interviews, questionnaires, and literatures. Location of this study was at PLT/D Pesanggaran. The data that were gathered is used to be the base for value determination from valuation categories, so that the value of effectiveness of EIA application in PLTD/G Pesanggaran is subsequently gained. The EIA implementation of PLTD/G Pesanggaran as a whole was sufficient and in accordance with the environmental document. Supervision of RKL-RPL implementation which was done by BLH had been carried out systematically and effectively. The effectiveness value of EIA implementation in PLTD/G Pesanggaran was 94%, which means that the EIA implementation was effective.